The labor issue in the USA in the first half of the 20th century. The contribution of the Catholic Church to its solution - Graban, Marcin (Annales. Etyka w Życiu Gospodarczym, 2019)
The stance of the Catholic Church in the United States of America on the problems related to workers’ wages is an interesting issue from the point of view of the ethics of economic life and the development of Catholic social thought. The interpretation of the main Catholic social ideas contained in Leo XIII’s encyclical letter Rerum novarum was made by Father John Augustine Ryan (1896–1945), who soon became a major proponent of the idea that a good economic policy can only result from good ethics. In the history of the United States of America, the turn of the 19th and 20th centuries was a time of the development of labor unions, associations and workers’ organizations as well as the consolidation of efforts to achieve equitable remuneration (a living wage) and regulate working conditions. It was also a time of struggling with the ideas of socialism and nationalism. The Catholic Church played a significant role in the discourse on these issues, including the influence of John A. Ryan. His efforts led to one of the most important interpretations of economic life: The Program of Social Reconstruction (1919), and some of its postulates can be found in the New Deal legislation.